2018
DOI: 10.1177/0095244318783024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and thermal kinetic analysis of pineapple leaf fibers and their reinforcement in epoxy

Abstract: The progress in the development of composites with natural fibers for various applications in different sectors witnesses remarkable success worldwide in the last decade. Among the various natural fibers existing worldwide, pineapple leaf fibers (PALFs) possess remarkable mechanical properties because of the maximum content of cellulose (*80%) among all natural fibers. In spite of having few limitations such as hydrophilicity, its advantages such as low cost, low weight, and biodegradability overweigh their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 49 publications
(73 reference statements)
1
18
0
Order By: Relevance
“…Sheng and Gimbun found that an increment in the fiber volume fraction increases the flexural strength linearly from 4% to 6% up to 0.4 fiber fraction [10]. Jain et al varied the fiber fraction from 0.1 to 0.3 and found that there is increment in tensile strength and flexural strength by 3-8% [11]. Chollakup et al used the different fibers and found that PALF and banana fiber provides better mechanical and thermal properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…Sheng and Gimbun found that an increment in the fiber volume fraction increases the flexural strength linearly from 4% to 6% up to 0.4 fiber fraction [10]. Jain et al varied the fiber fraction from 0.1 to 0.3 and found that there is increment in tensile strength and flexural strength by 3-8% [11]. Chollakup et al used the different fibers and found that PALF and banana fiber provides better mechanical and thermal properties [12].…”
Section: Introductionmentioning
confidence: 99%
“…The loading of PALF was fixed at 10% by weight, and the thickness of composite produced was 3 mm. The respective PALF loading was chosen based on previous studies affirming its high mechanical properties [ 17 ]. As for the hybrid composite, the weight of PALF is 5% wt because it has glass fiber mat on the top and bottom layers of the composite.…”
Section: Methodsmentioning
confidence: 99%
“…Isocyanates are organic compounds that contain the isocyanate functional group R-N¼C¼O. These groups have high reactivity toward hydroxyl groups forming urethane linkages, as shown in equation (11). These are used to remove the hydroxyl groups on cellulose and lignin.…”
Section: Isocyanate Treatmentmentioning
confidence: 99%